(untitled) - Western Wood Products Association (Portland, Or., 1973)
Western Woods Use Book: Structural Data & Design Tables [Hardcover] [Jan 01, 1973] Western Wood Products Association.
Keywords: Building, Wooden,Xây dựng, Gỗ; Tables,Bàn